Fluoroless versus conventional ureteroscopy: clinical outcomes, stone-free rate and complications - Zorrilla, Ricardo C.; Arroyo, Carlos M.; Vázquez, Rosa P. V.; Yañez, César E. V.; Bahena, Pedro A. A.; Anceno, Alec; Martínez, Marco A. A.; Castillo, Ricardo D.; Ramírez, Daniel A.; Orozco, Mauricio C.; Noyola, Gerardo F.; Montor, Jorge G. M.; et al. (International Surgery Journal, 2025)
Background: Urinary lithiasis is a prevalent condition worldwide, with recurrence rates up to 50% within five years. Ureteroscopy (URS) and retrograde intrarenal surgery (RIRS) are the preferred treatments for stones smaller than 20 mm, often involving radiation exposure. Fluoroless ureteroscopy (F-URS) has emerged as a potential method to reduce radiation-related risks for patients and healthcare personnel. Methods: A retrospective, observational study was conducted, including patients over 18 years with ureteral or renal lithiasis treated with either F-URS (April 2022 to January 2023) or conventional ureteroscopy (C-URS) with fluoroscopy (January 2023 to January 2024). Data on stone-free rates (SFR), complications, surgical time, and radiation exposure were analyzed. Nominal variables were described with absolute and relative frequencies, while numerical variables were analyzed using means and standard deviations. Statistical comparisons were made using odds ratios (OR) with 95% confidence intervals (CI) and the Mann-Whitney U test. Results: A total of 369 patients were included: 164 (44.44%) in the F-URS group and 205 (55.56%) in the C-URS group. The overall SFR was 76.96% (80.49% in F-URS versus 74.15% in C-URS; OR 0.70, 95% CI 0.42-1.14, p=0.152). Surgical time was longer in the C-URS group (75.15±41.34 min) compared to the F-URS group (65.59±36.03 min). Complication rates were similar between groups (15.85% versus 12.20%; OR 0.74, 95% CI 0.41-1.33, p=0.313). Radiation exposure for fourth-year residents averaged 1.17 mGy, decreasing progressively with training level. Conclusions: F-URS is a safe and effective technique for treating ureteral and renal lithiasis, with comparable SFR and complication rates to conventional ureteroscopy. The reduction in radiation exposure benefits both patients and surgical staff. Although current guidelines do not explicitly endorse F-URS, it should be considered in teaching hospitals and complex cases where radiation minimization is a priority.